Negative electrode sheet, secondary battery and negative electrode sheet volume expansion rate qualified prediction method

By using graphite and silicon-containing materials in the negative electrode sheet of the secondary battery, combined with silicon oxygen or silicon carbon materials, the problem of high volume expansion rate of the negative electrode material of the secondary battery is solved, and low volume expansion rate and high The effect of cycle life.

CN116111048BActive Publication Date: 2025-02-21REPT BATTERO ENERGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310137193.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2025-02-21
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

The theoretical capacity of the negative electrode material graphite used in secondary batteries has reached its limit, and the silicon-containing material leads to a high volume expansion rate during the lithium embedding process, limiting the cycling performance of the secondary battery.

Method used

The negative electrode sheet is adopted, and its active materials include graphite and silicon-containing materials. The silicon material matrix is ​​silicon oxygen or silicon carbon material. The silicon single plasmon particle size is less than 10nm. The volume expansion rate of the negative electrode sheet is controlled through specific preparation methods and composition ratios. , and predict the volume expansion rate by detecting the lithium-embedded phase change peak of the capacity increment curve.

Benefits of technology

The low volume expansion rate of the negative electrode sheet after 1000 cycles is achieved, which extends the cycle life of the secondary battery and increases the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116111048B_ABST
    Figure CN116111048B_ABST
Patent Text Reader

Abstract

The present application relates to the field of battery technology, and in particular to a negative electrode plate, a secondary battery, and a method for predicting the qualified volume expansion rate of a negative electrode plate. The negative electrode plate provided in the present application includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, the negative electrode film layer includes a negative electrode active material, the negative electrode active material includes graphite and a silicon-containing material, the silicon-containing material includes a silicon material matrix and a silicon single substance dispersed in the silicon material matrix, and the particle size of the silicon single substance is <10nm; the negative electrode plate meets the following requirements: when the negative electrode plate and a lithium metal plate are combined into a button battery, and the button battery is discharged to 5mV at 0.05C, its capacity increment curve has a silicon lithium insertion phase change peak at the position of 0.15V to 0.165V. The negative electrode plate that meets the above conditions has a low volume expansion rate and a high capacity. After 1000 cycles, the expansion rate is still less than 82%, which can enable the secondary battery to maintain a high battery capacity for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode plate, a secondary battery, and a method for predicting the qualified volume expansion rate of a negative electrode plate. Background Art

[0002] In recent years, with the popularization of portable electronic devices and the vigorous development of new energy electric vehicles, the development of high energy density secondary batteries has become increasingly important from the perspective of pursuing portability and applicability. At present, the negative electrode used in secondary batteries is mainly graphite materials, whose theoretical capacity is only 372mAh / g, and has been developed to the limit of the material, and gradually no longer meets the requirements of high energy density secondary batteries. Therefore, it is urgent to develop a new secondary battery negative electrode system. The capacity of single silicon is 3579mAh / g, which can be used as a preferred negative electrode material for high energy density secondary batteries. However, during the lithium insertion process, silicon particles are severely deformed in volume, and the volume expansion is as high as 400%, which leads to the expansion and contraction of the electrode. With the excessive reduction of the electrolyte and the formation of a solid electrolyte interface film, the battery capacity decays rapidly. After optimization, the silicon-oxygen material still has a 200% volume expansion, which seriously limits the cycle performance of the secondary battery. Summary of the invention

[0003] The embodiments of the present application provide a negative electrode plate with a low volume expansion rate, a secondary battery prepared therefrom, and a method for predicting the qualified volume expansion rate of a negative electrode plate using a silicon-containing material, so as to solve the problem in the related art that the volume expansion rate of the negative electrode plate is high and the cycle performance of the secondary battery is poor due to the use of silicon-containing materials.

[0004] The applicant has found that if a negative electrode plate containing silicon material is used to form a button battery with a lithium metal plate, and the button battery is discharged at 0.05C to 5mV, and its capacity increment curve can be detected to have a silicon lithium insertion phase change peak at the position of 0.15V to 0.165V, the volume expansion rate of the secondary battery containing the negative electrode plate is still less than 82% after 1000 cycles, so that the secondary battery can maintain a high battery capacity for a long time.

[0005] Based on the above findings, this application provides the following technical solutions:

[0006] In a first aspect, the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material, the negative electrode active material includes graphite and a silicon-containing material, the silicon-containing material includes a silicon material matrix and silicon单质 dispersed in the silicon material matrix, the silicon material matrix is a silicon oxide material or a silicon carbide material, and the particle size of the silicon单质 < 10 nm; the negative electrode plate satisfies that when the negative electrode plate and a lithium metal sheet are formed into a button cell and the button cell is discharged to 5 mV at 0.05 C, its capacity increment curve has a lithium insertion phase transition peak of silicon at the position of 0.15 V to 0.165 V.

[0007] The negative electrode active material of the present application includes graphite and a silicon-containing material. The silicon-containing material includes a silicon material matrix and silicon单质 dispersed in the silicon material matrix. The silicon material matrix is a silicon oxide material or a silicon carbide material, and the particle size of the silicon单质 < 10 nm. When the particle size of the silicon单质 is too large, the internal expansion stress of the silicon-containing material is uneven, resulting in the cracking of the silicon-containing material particles, exposing a large number of fresh interfaces to react with the electrolyte to generate a large amount of by-products, resulting in excessive swelling of the negative electrode plate and accelerated cycle decay.

[0008] In some preferred embodiments, the particle size of the silicon单质 is 1 to 8 nm; further preferably, the particle size of the silicon单质 < 5 nm; more preferably, the particle size of the silicon单质 is 2 to 3 nm. When the particle size of the silicon单质 is greater than 10 nm, the lithium insertion phase transition peak of silicon in its capacity increment curve is not in the range of 0.15 V to 0.165 V, which will cause excessive swelling of the negative electrode plate and accelerated cycle decay.

[0009] In some embodiments, the silicon单质 is generated by the disproportionation reaction of silicon monoxide during the preparation of the silicon oxide material, or is generated by the chemical vapor deposition of a silicon source during the preparation of the silicon carbide material; preferably, the silicon source is silane.

[0010] In some embodiments, when the silicon material matrix is a silicon oxide material, the preparation method of the silicon-containing material is: reacting SiO X powder (0 < X < 2) and lithium hydroxide hydrate at 800 - 1300 °C in an inert atmosphere to obtain the silicon-containing material.

[0011] In some embodiments, when the silicon material matrix is a silicon carbide material, the preparation method of the silicon-containing material is: when the silicon material matrix is a silicon carbide material, the preparation method of the silicon-containing material is: using a porous carbon matrix as a substrate material, introducing a silicon source for chemical vapor deposition, so that nano-silicon particles are deposited in the through-holes of the porous carbon matrix and on the outer surface of the porous carbon matrix; finally, carbon coating is performed on the chemical vapor deposition product.

[0012] In some embodiments, the mass proportion of the silicon-containing material in the negative electrode active material is 2%-50%. When the mass proportion of the silicon-containing material in the negative electrode active material exceeds 50%, the expansion rate of the negative electrode plate will be too high after the negative electrode plate has been cycled for 1000 times. The mass proportion of the silicon-containing material meets the above conditions, which can increase the specific capacity of the negative electrode, thereby increasing the energy density of the battery. At the same time, the effect of the addition of silicon-containing material in this range on the structural stability of the negative electrode plate is within a controllable range, which can ensure that the battery maintains a long cycle life. In some preferred embodiments, the mass proportion of the silicon-containing material in the negative electrode active material is 2% to 30%; more preferably, the mass proportion of the silicon-containing material in the negative electrode active material is 2 to 10%; further preferably, the mass proportion of the silicon-containing material in the negative electrode active material is 3 to 8%.

[0013] In some embodiments, the specific surface area of ​​the silicon-containing material is 1 to 8 m 2 / g. Too large a specific surface area of ​​the silicon-containing material will cause the particle surface to react with the electrolyte during the cycle to generate too many byproducts, resulting in accelerated cycle decay. In some preferred embodiments, the specific surface area of ​​the silicon-containing material is 1.5 to 3.0 m 2 / g.

[0014] In some embodiments, the (Dv90-Dv10) / Dv50 of the silicon-containing material satisfies: 1 to 1.3. (Dv90-Dv10) / Dv50 represents the particle concentration of the material. If the particle concentration is too small, it indicates that the particles are strictly screened during the manufacturing process and the production capacity is low. If the particle concentration is too large, it means that there are more large and small particles, which will lead to poor particle arrangement in the negative electrode sheet, uneven distribution of the porosity of the electrode sheet, poor dynamics in some areas of the cycle process, and severe cases may cause local lithium deposition in the electrode sheet in the late stage of the cycle. In some preferred embodiments, the particle concentration (Dv90-Dv10) / Dv50 of the silicon-containing material satisfies: 1 to 1.1.

[0015] In some embodiments, the bonding force F between the negative electrode film layer and the negative electrode current collector satisfies: F = 7-100 N / m. If the bonding force F between the negative electrode film layer and the negative electrode current collector is too low (less than 7 N / m), it is easy to cause the negative electrode film layer to delithium after cycling, causing the current collector cycle to deteriorate; F greater than 100 N / m indicates that excessive bonding force affects the dynamics. In some preferred embodiments, the bonding force F between the negative electrode film layer and the negative electrode current collector satisfies: 10 N / m ≤ F ≤ 30 N / m. More preferably, 10 N / m ≤ F ≤ 20 N / m.

[0016] In a second aspect, the present application provides a method for predicting the qualified volume expansion rate of a negative electrode plate, comprising the following steps:

[0017] The negative electrode plate and the lithium metal plate are combined into a button battery;

[0018] The button cell is discharged at 0.05C to 5mV. If it is detected that the capacity increment curve of the button cell has a lithium insertion phase transition peak of silicon at the position of 0.15V to 0.165V, the volume expansion rate of the negative electrode plate is qualified.

[0019] In a third aspect, the present application provides a secondary battery comprising the above-mentioned negative electrode plate.

[0020] In some embodiments, the secondary battery also includes a positive electrode plate, the positive electrode plate includes a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material of the positive electrode of the battery is selected from one or more of LiCoO2, LiNiO2, LiFePO4, LixNiyM1-yO2, wherein 0.9≤x≤1.2, 0.5≤y<1, and M is selected from one or more of Co, Mn, Al, Mg, Ti, Fe, Cr, Mo, and Ca.

[0021] In some embodiments, the positive electrode active material of the battery positive electrode is LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0022] The beneficial effects of the technical solution provided by the present application include: the present application finds that the negative electrode sheet using silicon-containing materials meets certain test results and has a low volume expansion rate after 1000 cycles, so a negative electrode sheet that meets the test results is provided to maintain the cycle life of the secondary battery. The negative electrode sheet uses silicon-containing materials, which has a higher energy density than pure graphite negative electrode sheets, and avoids the problem of rapid attenuation of secondary battery capacity and short cycle life due to the high volume expansion rate of negative electrode sheets that do not meet the test results, which greatly helps the portability and applicability of portable electronic devices and new energy electric vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 The capacity increment curve V-dQ / dV diagram of the button battery composed of the negative electrode plate and the lithium metal plate provided in Example 1 of the present application is discharged to 5mV at 0.05C. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0026] The term "particle concentration" in this application represents (Dv90-Dv10) / Dv50, wherein Dv10 is the particle size corresponding to 10% of the volume distribution, Dv50 is the particle size corresponding to 50% of the volume distribution, and Dv90 is the particle size corresponding to 90% of the volume distribution.

[0027] Unless otherwise specified, the test method used in this application to determine the particle size of silicon is as follows:

[0028] 1. Place the sample to be tested on the X-ray sample holder.

[0029] 2. Adjust the optical path of the goniometer and calibrate its zero position and angle reading according to the instructions of the X-ray diffractometer.

[0030] 3. X-rays use CuKα radiation, and CuKβ radiation is removed by filters or monochromators.

[0031] 4. The operating voltage of the X-ray tube is 30-35KV, the operating current is 15-20mA, the counter scanning speed is 1 / 4° / min, and the scanning range is 10-80°.

[0032] 5. Calculate the particle size of silicon at the silicon peak (28.4°) using the Scherrer formula

[0033]

[0034] K is the Scherrer constant. If B is the half-peak width of the diffraction peak, K = 0.89; if B is the integrated height and width of the diffraction peak, K = 1;

[0035] D is the average thickness of the grain perpendicular to the crystal plane That is, the particle size of silicon element;

[0036] B is the half-height width of the measured sample diffraction peak (double-line correction and instrument factor correction must be performed), which needs to be converted into radians (rad) during the calculation process;

[0037] θ is the Bragg diffraction angle, in degrees;

[0038] γ is the wavelength of X-rays,

[0039] An embodiment of the present application provides a negative electrode sheet including a negative electrode active material composed of graphite and a silicon-containing material. The negative electrode sheet has a low volume expansion rate and can solve the problem in the related art that the cycle life of a secondary battery is poor due to the high volume expansion rate of the negative electrode sheet using a silicon-containing material.

[0040] The negative electrode sheet provided by the present application includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. The negative electrode film layer includes a negative electrode active material, the negative electrode active material includes graphite and a silicon-containing material, the silicon-containing material includes a silicon material matrix and silicon elemental substances dispersed in the silicon material matrix, the silicon material matrix is a silicon oxide material or a silicon carbide material, and the particle size of the silicon elemental substances is <10 nm; the negative electrode sheet satisfies: when the negative electrode sheet and a lithium metal sheet are formed into a button cell, and the button cell is discharged to 5 mV at 0.05C, the capacity increment curve has a lithium insertion phase transition peak of silicon at the position of 0.15V - 0.165V.

[0041] The negative electrode current collector used in the present application is not particularly limited as long as the object of the present application can be achieved. The negative electrode current collector used in the embodiment of the present application is a copper foil.

[0042] The method for forming a button cell by combining the negative electrode sheet and a lithium metal sheet in the present application: Assemble a negative electrode sheet wafer, a separator, and a lithium metal wafer, and add an electrolyte to prepare a button cell. The solvent of the electrolyte is a mixed solution of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) with a volume ratio of 1:1:1, and the solute is LiPF6 with a concentration of 1 mol / L.

[0043] The temperature for discharging the button cell to 5 mV at 0.05C is 25 ± 5°C.

[0044] In the embodiment provided by the present application, (Dv90 - Dv10) / Dv50 of the silicon-containing material satisfies: 1 - 1.3.

[0045] In some embodiments of the present application, when the silicon material matrix is a silicon oxide material, the preparation method of the silicon-containing material is: React SiOx powder (0 < X < 2) and lithium hydroxide hydrate at 800 - 1300°C in an inert atmosphere to obtain a silicon-containing material with a silicon oxide material as the silicon material matrix. Specifically, place a mixture of SiOx powder (0 < X < 2) and lithium hydroxide hydrate with a weight ratio of 90:10 - 80:20 in a silicon nitride tray and put it in a reaction furnace. While argon flows through the furnace at a flow rate of 10 - 20 NL / min, react at a temperature of 800 - 1300°C for 2 - 5 hours to obtain unprocessed lithium-containing silicon oxide powder. Grind the unprocessed lithium-containing silicon oxide powder in an alumina ball mill, using alumina balls as the grinding medium and hexane as the solvent, to grind and obtain lithium-containing silicon oxide powder with a particle size of 1 - 10 μm, which is the silicon-containing material.

[0046] When the silicon material matrix is ​​a silicon-carbon material, the preparation method of the silicon-containing material is: using a porous carbon matrix as a base material, introducing a silicon source for vapor deposition, so that nano-silicon particles are deposited in the through holes and on the outer surface of the porous carbon microspheres, and finally carbon-coating the vapor-deposited product. Specifically: using a porous carbon matrix as a base material, using silicon-containing gas silane as a silicon source, and nitrogen as a protective gas, vapor deposition is performed in a rotary furnace, the silicon-containing gas flow rate is 0.5L-20 / min, the protective gas flow rate is 1-20L / min, the vapor deposition temperature is 500-1000°C, the vapor deposition time is 5-15 hours, and then the obtained vapor deposition product is carbon-coated to obtain a silicon-containing material.

[0047] As the silicon-containing material decays, the gram capacity after delithiation will gradually decrease, and the material is generally characterized by the gram capacity after the first delithiation to 1.5V. In the embodiments provided in the present application, the gram capacity of the silicon-containing material after the first delithiation to 1.5V is 1300-2400mAh / g. In some preferred embodiments, the gram capacity of the silicon-containing material after the first delithiation to 1.5V is 1350-2000mAh / g.

[0048] In the embodiments provided in the present application, the negative electrode active material is composed of graphite and silicon-containing material, the peak intensity of the lithium insertion phase change peak of silicon is -2Ah / V / g to -10Ah / V / g, and the mass proportion of silicon-containing material in the negative electrode active material is 2% to 50%.

[0049] The present application provides a method for predicting whether the volume expansion rate of a negative electrode plate is qualified, comprising the following steps: the above negative electrode plate and a lithium metal plate are combined into a button battery; the button battery is discharged at 0.05C to 5mV, and if it is detected that the capacity increment curve of the button battery has a silicon lithium insertion phase change peak at the position of 0.15V to 0.165V, then the volume expansion rate of the negative electrode plate is detected to be qualified.

[0050] The volume expansion rate of different silicon additions in the industry is different, and the expansion rate of the pole pieces of different structures and chemical systems of battery cells is different. This volume expansion rate qualified test method is applicable to the negative pole piece provided in this application.

[0051] The present application also provides a method for preparing the negative electrode sheet, comprising the following steps:

[0052] Step S101, dispersing graphite, silicon-containing material, conductive agent, binder, and additive in a solvent and stirring evenly to obtain a negative electrode slurry;

[0053] Step S102, coating the negative electrode slurry on at least one surface of the negative electrode current collector, drying and cold pressing to obtain a negative electrode sheet.

[0054] The present application also provides a secondary battery, which includes the above-mentioned negative electrode sheet, positive electrode sheet and electrolyte. The positive electrode sheet may include a positive electrode collector and a positive electrode film layer disposed on at least one surface of the positive electrode collector and containing a positive electrode active material.

[0055] The negative electrode plate provided in the present application and the secondary battery prepared therefrom are described in detail below in conjunction with the embodiments.

[0056] Unless otherwise specified, the silicon-containing materials used in Examples 2, 4, 6, 8, 9 and Comparative Examples 1, 2, 3, 4 are silicon-oxygen materials, which are prepared as follows: SiO2 in a weight ratio of 85 to 95:10 is placed in a silicon nitride tray. 1.05 A mixture of powder and lithium hydroxide hydrate (by adjusting SiO 1.05 The ratio of powder and lithium hydroxide hydrate can obtain silicon-containing materials of different gram capacities in Table 1), and is placed in a reaction furnace; while argon flows through the furnace at a flow rate of 10NL / min, it is reacted at a temperature of 800-1200°C for 3-10 hours, and after cooling, it is ground in an alumina ball mill, using alumina balls as grinding media and hexane as solvent during the grinding process to obtain silicon-containing materials with a particle size of 1-10μm. Different embodiments control the particle size of silicon element by controlling the reaction temperature and reaction time: the higher the reaction temperature and the longer the reaction time, the larger the particle size of silicon element. Therefore, silicon element with a fixed particle size in each embodiment and comparative example can be obtained by controlling the reaction temperature and time.

[0057] The silicon-containing materials used in Examples 1, 3, 5, 7, and 10 are silicon-carbon materials, all of which are prepared as follows: a porous carbon matrix is ​​used as a substrate, silicon-containing gas silane is used as a silicon source, and nitrogen is used as a protective gas, and vapor deposition is performed in a rotary furnace. The silicon-containing gas flow rate is 0.5 L / min, the protective gas flow rate is 1 L / min, the vapor deposition temperature is 500-1000°C, and the vapor deposition time is 5-15 hours; the obtained vapor deposition product is then carbon-coated to obtain a silicon-containing material. Different embodiments control the size of the silicon element particle size by controlling the vapor deposition temperature and the vapor deposition time. The higher the vapor deposition temperature and the longer the vapor deposition time, the larger the silicon element particle size. Therefore, the silicon element with a fixed particle size in each embodiment can be obtained by controlling the vapor deposition time and temperature.

[0058] Embodiment 1:

[0059] Embodiment 1 of the present application provides a negative electrode plate and a lithium-ion secondary battery, and the preparation methods of the negative electrode plate and the lithium-ion secondary battery are as follows:

[0060] Preparation of negative electrode sheet:

[0061] The negative electrode active material (composed of graphite and silicon-containing material in a weight ratio of 94.1:2), styrene-butadiene rubber, sodium carboxymethyl cellulose, carbon black (SuperP) and single-walled carbon nanotubes (SWCNT) are fully stirred and mixed in deionized water in a mass ratio of 96:0.5:2.5:0.95:0.05 to form a uniform negative electrode slurry; the negative electrode slurry is coated on the surface of the negative electrode current collector copper foil, and the negative electrode sheet is obtained after drying, cold pressing, striping and cutting.

[0062] Preparation of positive electrode sheet:

[0063] Lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), carbon nanotubes (CNT) and carbon black (SuperP), and binder PVDF are fully stirred and mixed in NMP at a mass ratio of 97:1:1:1 to form a uniform positive electrode slurry; the positive electrode slurry is coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.

[0064] Prepare electrolyte:

[0065] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and then LiPF6 is uniformly dissolved in the mixed solvent to obtain an electrolyte with a LiPF6 concentration of 1 mol / L.

[0066] Preparation of lithium-ion secondary batteries:

[0067] The positive electrode sheet, polyethylene (PE) film, and negative electrode sheet are stacked in order, and a reference electrode is added between the polyethylene (PE) film and the negative electrode sheet (the reference electrode is used for subsequent performance testing of the battery sample, and a lithium sheet, lithium metal wire, etc. can be selected, and the reference electrode should be separated by an isolation film to prevent contact with either side of the positive and negative electrodes). After winding, an electrode assembly is obtained; the electrode assembly is added to an outer package, and the electrolyte of the peak position test step of the lithium insertion phase change peak is added. After packaging, standing, formation, aging and other processes, a lithium-ion secondary battery is obtained.

[0068] The preparation methods of Examples 2 to 9 are similar to those of Example 1, with the same design parameters for the positive electrode sheets and different preparation and design parameters for the negative electrode sheets. The specific differences are described below and Table 1.

[0069] The negative electrode material formulation and preparation of Example 2 are the same as those of Example 1, except that the design parameters are different (see Table 1).

[0070] The formula of Examples 3 and 4 is: negative electrode active material (composed of graphite and silicon-containing material in a weight ratio of 85.5:9.5), styrene-butadiene rubber, sodium carboxymethyl cellulose, carbon black (Super P) and single-walled carbon nanotubes (SWCNT) in a weight ratio of 95:0.8:3.2:0.9:0.1. The other steps and settings of Examples 3 and 4 are the same as those of Example 1; the difference also lies in the different design parameters (see Table 1).

[0071] The formula of Examples 5 and 6 is: negative electrode active material (composed of graphite and silicon-containing material in a weight ratio of 75.2:18.8), styrene-butadiene rubber, sodium carboxymethyl cellulose, carbon black (SuperP) and single-walled carbon nanotubes (SWCNT) in a mass ratio of 94:1:4:0.9:0.1. The other steps and settings of Examples 5 and 6 are the same as those of Example 1, except that the design parameters are different (see Table 1).

[0072] The formula of Examples 7 and 8 is: negative electrode active material (composed of graphite and silicon-containing material in a weight ratio of 65.1:27.9), styrene-butadiene rubber, sodium carboxymethyl cellulose, carbon black (SuperP) and single-walled carbon nanotubes (SWCNT) in a mass ratio of 93:1:5:0.85:0.15. The other steps and settings of Examples 7 and 8 are the same as those of Example 1, except that the design parameters are different (see Table 1).

[0073] The formula of Examples 9 and 10 is: negative electrode active material (composed of graphite and silicon-containing material in a weight ratio of 56.8:37.2), styrene-butadiene rubber, sodium carboxymethyl cellulose, carbon black (SuperP) and single-walled carbon nanotubes (SWCNT) in a mass ratio of 94:1:5:0.8:0.2. The other steps and settings of Examples 9 and 10 are exactly the same as those of Example 1, except that the design parameters are different (see Table 1).

[0074] The preparation methods of Comparative Examples 1 to 4 are similar to those of Example 1, except that the design parameters of the negative electrode sheet and the positive electrode sheet are different. The different product parameters are detailed in Table 1.

[0075] The negative electrode sheets and lithium-ion secondary batteries of Examples 1 to 10 and Comparative Examples 1 to 4 were subjected to performance tests, and the test process included:

[0076] (1) Peak position test of lithium insertion phase transition peak

[0077] Preparation of button cells: Take the negative electrode sheets in the above Examples 1 to 10 and Comparative Examples 1 to 4, respectively use metal lithium sheets as counter electrodes and polyethylene (PE) films as separators. Mix ethylene carbonate (EC), ethyl methyl carbonate (EMC), and ethyl carbonate (DEC) in a volume ratio of 1:1:1 to obtain a mixed solvent, then evenly dissolve LiPF6 in the mixed solvent to obtain an electrolyte with a LiPF6 concentration of 1 mol / L, and assemble into CR2032 button cells in an argon-protected glove box.

[0078] After the obtained button battery was left to stand for 8 hours at 25°C, it was discharged at a constant current of 0.05C to a voltage of 5.0mV, and the voltage and capacity data were collected; then the SLOPE function was used in EXCEL to calculate dQ / dV; the capacity increment curve V-dQ / dV graph was drawn according to the obtained voltage and dQ / dV data, and the peak position of the corresponding phase change peak was obtained. The capacity increment curve V-dQ / dV graph of the button battery composed of the negative electrode sheet of Example 1 is shown in Figure 1 .

[0079] (2) Cycle life test

[0080] At 25°C, the lithium ion secondary batteries prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were charged at a constant current of 1C to a charge cut-off voltage of 4.2V, then charged at a constant voltage to a current of 0.05C, left to stand for 10 minutes, and then discharged at a constant current of 1C to a discharge cut-off voltage of 2.8V, and the initial capacity was recorded as C. Then, the lithium ion secondary batteries were charged at a constant current of 1C to a charge cut-off voltage of 4.2V, then charged at a constant voltage to a current of 0.05C, left to stand for 10 minutes, and then discharged at a constant current of 1C to a discharge cut-off voltage of 2.8V, and the discharge capacity of each cycle was recorded as C. n , until the cycle capacity retention rate (C n / C*100%) is 80%, and the number of cycles is recorded. The more cycles, the longer the cycle life of the battery.

[0081] (3) Thickness test

[0082] The lithium-ion secondary batteries in Examples 1 to 10 and Comparative Examples 1 to 4 are charged at room temperature at a constant current of 1C to a charging cut-off voltage of 4.2V, then charged at a constant voltage to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 1C to 2.8V. Repeat the above steps 1000 times. Then, charge at a constant current of 1C to a charging cut-off voltage of 4.2V, then charge at a constant voltage to a current of 0.05C to obtain a fully charged battery, and then take its negative electrode plate for thickness testing. The plate expansion rate = (plate thickness after 1000 cycles - plate thickness before cycle) / (plate thickness before cycle - copper foil thickness). The smaller the plate expansion rate value, the smaller the volume change of the negative electrode plate.

[0083] The test results of Examples 1 to 10 and Comparative Examples 1 to 4 are shown in Table 1.

[0084] Table 1: Test results of Examples 1 to 10 and Comparative Examples 1 to 4

[0085]

[0086]

[0087] Note: The gram capacity (mAh / g) of silicon-containing materials refers to the gram capacity after the first delithiation to 1.5V.

[0088] Figure 1 In the figure, number 1 indicates that the capacity increment curve V-dQ / dV has a silicon lithium insertion phase transition peak at 0.15 to 0.165 V. It can be seen that the lithium ion secondary battery prepared in Example 1 has a silicon lithium insertion phase transition peak at 0.15 to 0.165 V, thereby making the negative electrode sheet have a higher reversible capacity and alleviating the volume change of the negative electrode sheet to a certain extent, thereby significantly improving the energy density and effectively improving the cycle performance of the lithium ion secondary battery.

[0089] In Table 1, it can be seen from the data of Example 9 and Comparative Example 1 that the particle size of silicon in the silicon-containing material is less than 10nm, the peak position of the silicon-embedded lithium phase change peak is in the range of 0.15V to 0.165V, the cycle performance is high, and the expansion rate of the negative electrode plate is low; it can be seen from the data of Example 9 and Comparative Example 2 that when the particle concentration (Dv90-Dv10) / Dv50 of the silicon-containing material satisfies 1 to 1.3, there are few side reactions in the battery, the peak position of the silicon-embedded lithium phase change peak is in the range of 0.15V to 0.165V, the expansion rate of the negative electrode plate is low, and the cycle performance is good; it can be seen from the data of Example 9 and Comparative Example 3 that the bonding force F between the negative electrode film layer and the negative electrode current collector satisfies: 7N / m≤F, the peak position of the silicon-embedded lithium phase change peak is in the range of 0.15V to 0.165V, the cycle performance of the lithium-ion secondary battery is improved, and the expansion rate of the negative electrode plate is low; it can be seen from the data of Example 1 and Comparative Example 4 that the specific surface area of ​​the silicon-containing material satisfies <3m 2 / g, the peak position of silicon-intercalated lithium phase change peak is in the range of 0.15V to 0.165V, and the cycle life and the expansion rate of the negative electrode sheet meet the battery design requirements.

[0090] From Table 1 and Figure 1It can be seen that when the negative electrode active material of the negative electrode plate includes graphite and silicon oxide material, and the negative electrode plate meets the following conditions: when the button cell composed of the negative electrode plate and the lithium metal plate is discharged to 0.005V at 0.05C, its capacity increment curve V-dQ / dV has a silicon lithium insertion peak at 0.15V to 0.165V, the secondary battery can take into account both low plate expansion and high cycle life. When the silicon single particle size is <10nm, the mass proportion of silicon-containing materials in the negative electrode active material is 2%-50%, and the specific surface area of ​​silicon-containing materials is <3m 2 / g, the tap density of silicon-containing materials is 0.85~1.45g / cm 3 The gram capacity of the silicon-containing material after the first lithium removal to 1.5V is 1300-2400mAh / g, the particle concentration of the silicon-containing material (Dv90-Dv10) / Dv50 satisfies: 1-1.3, and the gram capacity of the negative electrode active material is 380mAh / g-1550mAh / g. The bonding force F between the negative electrode film layer and the negative electrode current collector satisfies ≥7N / m, and the gram capacity of the negative electrode active material is within the range of 380mAh / g-1550mAh / g, which can further improve the cycle performance of the battery.

[0091] Since the comparative examples 1-4 do not meet the above conditions, it is difficult for the batteries to have both a long cycle life and small electrode expansion.

[0092] The positive electrode active materials of the embodiments of the present application only take lithium nickel cobalt manganese oxide (NCM811) as an example. Those skilled in the art can select different positive electrode active materials according to the actual use environment of the battery. For example, other types of lithium nickel cobalt manganese oxide (such as NCM622, NCM523, etc.), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium iron phosphate and carbon composite materials, and their respective modified compounds can be selected. When the negative electrode sheet of the present application is used in combination with the above-mentioned positive electrode active materials, a similar improvement effect can be achieved. No further details will be given here.

[0093] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.

[0094] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.

[0095] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A negative electrode plate, characterized in that: It comprises a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises a negative electrode active material, wherein the negative electrode active material comprises graphite and a silicon-containing material, wherein the silicon-containing material comprises a silicon material matrix and a silicon single substance dispersed in the silicon material matrix, wherein the silicon material matrix is ​​a silicon-oxygen material or a silicon-carbon material, and the particle size of the silicon single substance is less than 10 nm; the negative electrode pole piece satisfies: when the negative electrode pole piece and a lithium metal sheet are combined into a button battery, and the button battery is discharged to 5 mV at 0.05 C, its capacity increment curve has a lithium insertion phase change peak of silicon at a position of 0.15 V to 0.165 V; When the silicon material matrix is ​​a silicon-oxygen material, the preparation method of the silicon-containing material is: X The powder and lithium hydroxide hydrate react at 800-1300°C in an inert atmosphere to obtain a silicon-containing material, wherein 0 <X<2; When the silicon material matrix is ​​a silicon-carbon material, the preparation method of the silicon-containing material is: using a porous carbon matrix as a base material, introducing a silicon source for vapor deposition, so that nano-silicon particles are deposited in the through holes of the porous carbon matrix and on the outer surface of the porous carbon matrix; finally, carbon coating the vapor deposition product.

2. The negative electrode sheet according to claim 1, characterized in that: The silicon element is generated by disproportionation reaction of silicon monoxide during the preparation of silicon-oxygen materials, or by vapor deposition of silicon source during the preparation of silicon-carbon materials.

3. The negative electrode sheet according to claim 1, characterized in that: The mass proportion of the silicon-containing material in the negative electrode active material is 2%-50%.

4. The negative electrode plate according to claim 1, characterized in that: The specific surface area of ​​the silicon-containing material is 1 to 8 m 2 / g.

5. The negative electrode sheet according to claim 1, characterized in that: The (Dv90-Dv10) / Dv50 of the silicon-containing material satisfies: 1 to 1.

3.

6. The negative electrode plate according to claim 1, characterized in that: The bonding force F between the negative electrode film layer and the negative electrode current collector satisfies: F=7-100 N / m.

7. A method for predicting the qualified volume expansion rate of a negative electrode plate, characterized in that: The following steps are involved: The negative electrode sheet according to any one of claims 1 to 6 and a lithium metal sheet are combined into a button battery; The button cell is discharged at 0.05C to 5mV. If it is detected that the capacity increment curve of the button cell has a lithium insertion phase transition peak of silicon at the position of 0.15V to 0.165V, the volume expansion rate of the negative electrode plate is qualified.

8. A secondary battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet as claimed in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of silicon monoxide lithium ion battery negative electrode material and preparation method of battery negative plate

    CN111463423A

  • Three-dimensional network structure composite material for lithium battery and preparation method and application of three-dimensional network structure composite material

    CN115360355A